2023
DOI: 10.2459/jcm.0000000000001427
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic effects of heart rate lowering in patients admitted for acute heart failure: the RedRate-HF Study (Reduction of heart Rate in Heart Failure)

Abstract: Background In patients admitted for acute heart failure (HF) indication for drugs which reduce the heart rate (HR) is debated. The multicentre prospective study Reduction of heart Rate in Heart Failure (RedRate-HF) was designed to analyse the hemodynamic effects of an early reduction of HR in acute HF. Methods Hemodynamic parameters were recorded by using the bioimpedance technique, which was shown to be accurate, highly reproducible and sensitive to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Along with inflammatory marker indicators, several recent studies have shown the relationship between albumin, 34 tricuspid annular plane systolic excursion (TAPSE), 35 and output per beat 36 with heart failure. That suggested the importance of albumin supplementation in elderly men with heart failure 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Along with inflammatory marker indicators, several recent studies have shown the relationship between albumin, 34 tricuspid annular plane systolic excursion (TAPSE), 35 and output per beat 36 with heart failure. That suggested the importance of albumin supplementation in elderly men with heart failure 34 .…”
Section: Discussionmentioning
confidence: 99%